Concurrent infections in tiger grouper (Epinephelus fuscoguttatus) cultured in deep sea cages in Langkawi - Abdullah, Azila; Mansor, Nur Nazifah; Ramli, Rimatulhana; Ridzuan, Mohd Syafiq; Saad, Mohd Zamri; Abdullah, Siti Zahrah (2015)
Marine fish has been shown to be susceptible to parasites, bacteria, viral and fungal infections. In marine environment, Vibrio species are commonly found and can lead to an infection known as vibriosis. Vibriosis causes bloody lesion to the fish muscles and extensive haemorrhage to the internal organs to the marine fish. It is a zoonotic disease causing septicaemia, gastroenteritis and necrotising fasciitis following exposure of wounds to contaminated sea water or fish. In this study, we examined and sampled tiger grouper (Epinephelus fuscoguttatus ) cultured in deep sea cages until harvest time. The sampling period was started from February to August 2014, following more than 50% mortality. Clinical signs were noted and compared with the microbiological isolations, especially Vibrio spp. and specific viral isolations. Histopathology changes and water quality parameters were also noted. Fish infected with vibriosis showed signs of body ulcerations and haemorrhages of the fins and body with changes in the internal organs. Histopathology revealed lesions consisted of massive nodular lesions with dead neutrophils in accordance with infection by V. vulnificus. The prevalence rate of the 3 main Vibrio spp. (V. vulnificus, V. alginolyticus, and P. damselae) was between 50% to 90%. Concurrently, the affected fish also had VNN and iridovirus infections as detected by PCR. The iridovirus carrier status may influenced the prevalence of vibriosis, severity of lesions and rate of mortality throughout the studies.